2011
DOI: 10.1111/j.1460-9592.2011.03767.x
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual aid viewing immediately before pediatric induction moderates the accompanying parents’ anxiety

Abstract: Preoperative AVA shown to parents immediately before induction moderates the increase in anxiety associated with the anesthetic induction of their child. Present results suggest that behavioral characteristics seem better predictors of child's anxiety during induction than anxiety ratings per se and that anesthetists are better than parents in predicting child's anxiety during induction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 30 publications
0
29
0
6
Order By: Relevance
“…An evidence-based review of parental presence during induction found little anxiolytic influence of parents during transport to or within the OR 31 although there are data to suggest that parental presence became more common between the 1990s and 2000s. 33 The evaluation of other pediatric applications for video glasses might therefore benefit from a study arm for parents as well. Since the conclusion of our study, it has been reported that increases in parental anxiety are mitigated when children watch audio-visual cartoons with subject matter that prepares them for the perioperative experience.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…An evidence-based review of parental presence during induction found little anxiolytic influence of parents during transport to or within the OR 31 although there are data to suggest that parental presence became more common between the 1990s and 2000s. 33 The evaluation of other pediatric applications for video glasses might therefore benefit from a study arm for parents as well. Since the conclusion of our study, it has been reported that increases in parental anxiety are mitigated when children watch audio-visual cartoons with subject matter that prepares them for the perioperative experience.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%
“…Al ser un listado de comportamientos, algunos autores la han utilizado para determinar la ansiedad en el niño durante la inducción de la anestesia 34 . Ciertos comportamientos listados en esta escala se aprecian solo durante una inducción inhalatoria, como « gira la cabeza cuando se le acerca la mascarilla» o « se cubre la boca y la nariz con las manos y los brazos», por lo que varios artículos de esta revisión han modificado la herramienta para adaptarla a la realidad de la sala de inducción 35---37 .…”
Section: Discussionunclassified
“…Una inducción precaria fue considerada por sus autores como aquella que presentaba puntuaciones mayores de 6 25 , sin embargo, Varughese et al 38 sugirieron otra interpretación: inducción complaciente cuando el niño colabora durante la inducción de la anestesia sin ofrecer resistencia (ICC = 0), Cómo citar este artículo: Jerez C, et al «Evaluación de las escalas empleadas para determinar la ansiedad y el comportamiento del niño durante la inducción de la anestesia. Revisión 34,39 . La mYPAS 24 es la más utilizada, pues en sus 5 dimensiones engloba los comportamientos indicativos de ansiedad en el niño de 2-12 años durante el periodo perioperatorio 23,24 .…”
Section: Discussionunclassified
“…, , Berghmans et al . ). These interventions are effective at reducing anxiety in adolescents and their parents, but its spread could be seriously hampered by the accessibility, affordability and utility of supporting technologies.…”
Section: Introductionmentioning
confidence: 97%